Rates of antimicrobial resistance in latin america (2004-2007) and in vitro activity of the glycylcycline tigecycline and of other antibiotics - Rossi,Flávia (2008)
As a part of the Tigecycline Evaluation and Surveillance Trial (T.E.S.T.), Gram-positive and Gram-negative bacterial isolates were collected from 33 centers in Latin America (centers in Argentina, Brazil, Chile, Colombia, Guatemala, Honduras, Jamaica, Mexico, Panama, Puerto Rico, and Venezuela) from January 2004 to September 2007. Argentina and Mexico were the greatest contributors of isolates to this study. Susceptibilities were determined according to Clinical Laboratory Standards Institute guidelines. Resistance levels were high for most key organisms across Latin America: 48.3% of Staphylococcus aureus isolates were methicillin-resistant while 21.4% of Acinetobacter spp. isolates were imipenem-resistant. Extended-spectrum β-lactamase were reported in 36.7% of Klebsiella pneumoniae and 20.8% of E. coli isolates. Tigecycline was the most active agent against Gram-positive isolates. Tigecycline was also highly active against all Gram-negative organisms, with the exception of Pseuodomonas aeruginosa, against which piperacillin-tazobactam was the most active agent tested (79.3% of isolates susceptible). The in vitro activity of tigecycline against both Gram-positive and Gram-negative isolates indicates that it may be an useful tool for the treatment of nosocomial infections, even those caused by organisms that are resistant to other antibacterial agents.